1983
DOI: 10.1111/j.1471-4159.1983.tb08048.x
|View full text |Cite
|
Sign up to set email alerts
|

Species Heterogeneity of Pineal Hydroxyindole‐O‐Methyltransferase

Abstract: Hydroxyindole-O-methyltransferase was purified from bovine and chicken pineal glands to apparent homogeneity and their properties were compared. The purified enzymes from both pineal glands differed in electrophoretic mobility and isoelectric point. Sodium dodecyl sulfate gel electrophoresis revealed that hydroxyindole-O-methyltransferase of both bovine and chicken pineals was a dimer consisting of a subunit of molecular weight 39,000. The two enzymes also differed in substrate specificity. Bovine hydroxyindol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…1). A stmtlar molecular weight has been previously reported for chtcken and mammalian HIOMT (8). In addition, a mtnor ~mnunoreacttve pepttde of 28 kDa was observed tn chicken (Fig.…”
Section: Imnunoblot Analystssupporting
confidence: 67%
“…1). A stmtlar molecular weight has been previously reported for chtcken and mammalian HIOMT (8). In addition, a mtnor ~mnunoreacttve pepttde of 28 kDa was observed tn chicken (Fig.…”
Section: Imnunoblot Analystssupporting
confidence: 67%
“…This result indicates that excess N-acetylserotonin was not efficiently converted to melatonin by the sheep SNAT plus rice COMT cassette, unlike the Δ83riceSNAT plus rice COMT cassette, suggesting that the COMT-mediated methylation of N-acetylserotonin into melatonin was inhibited by high substrate levels. This type of substrate inhibition has been described in animal ASMTs (Nakane et al 1983). The peak melatonin production of 1465 ng/mL detected after 24 h in the dual sheep SNAT plus rice COMT expression cassette in E. coli was considerably greater than that of other heterologous host plants overexpressing either SNAT or ASMT.…”
Section: Melatonin Production In E Colimentioning
confidence: 92%
“…However, functional expression of animal ASMT in E. coli has been unsuccessful, as the recombinant ASMT proteins are insoluble and inactive (Ben-Abdallah et al 2011). In contrast, the plant ASMT proteins were only soluble and functional as a glutathione S-transferase (GST)-fusion form Zuo et al 2014), but the specific activity of GST-free recombinant ASMT is very low (0.21 pkat/mg protein) relative to that of chicken ASMT (3 nkat/mg protein) (Nakane et al 1983). In contrast to ASMT genes, SNAT genes, the product either from an animal or a plant, were functionally soluble in E. coli, but melatonin production in E. coli by SNAT combined with ASMT has not been possible due to either expression in an insoluble form or inadequate ASMT activity (BenAbdallah et al 2011;Park et al 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the cow, it has been suggested that the subunits could form polymers of a very high molecular weight (Jackson and Lovenberg, 1971). Immunochemical experiments have revealed a large heterogeneity in the protein structure and enzymatic properties among species (Nakane et al, 1983). The protein appears very stable (t 1/2 Ͼ 24 h) (Sugden et al, 1987b;Janavs et al, 1991;Bernard et al, 1993Bernard et al, , 1995Bernard et al, , 1996.…”
Section: G Hydroxyindole-o-methyltransferasementioning
confidence: 99%